Interpretasi Hakim dalam Menyelesaikan Sengketa Pelanggaran Myanmar terhadap Konvensi Genosida - Nisa’, Aulya; Nirwana, Nirwana; Kosho, Philippa Philomena (Balobe Law Journal, 2024)
Introductioan: A case of international dispute between Gambia and Myanmar where both countries have ratified the Convention on The Prevention of The Crime of Genocide.Purposes of the Research:  The purpose of the research is to identify the legal standing of the parties, analyze the judges’ interpretation of the dispute, and propose potential approaches to resolve this case.Methods of the Research: This research uses a qualitative approach to understand the issue under study, with legal analysis methods to evaluate legal aspects and case studies of Gambia vs. Myanmar.Results of the Research: Legal standing is important. With recognition as a legal subject and participation in international agreements. Then it can claim rights and demand obligations based on international law. In this paper, there are three relevant approaches that judges can use in resolving such dispute, namely geographical, political and humanitarian approaches. When the three are combined, it will enrich the legal analysis and possibly find the best solution for all international communities.